PENGARUH BEBAN KERJA TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI MEDIASI - Ayuningrum, Ni Kadek Adelia; Surya, Ida Bagus Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
The success or failure of a company in carrying out its duties and functions really depends on the individuals in the company, or human resources have a strategic role in determining the results of work achievements within a company. This study was conducted on employees of the HOMM Saranam Baturiti Hotel. This research aims to analyze the role of job satisfaction in mediating the influence of workload on turnover intention of HOMM Saranam Baturiti employees. The number of samples used was 62 employees using a saturated sample. Data collection was carried out using interview and questionnaire methods. The data analysis technique used is Path Analysis. Based on the results of the analysis, it was found that workload had a positive and significant effect on turnover intention, workload had a negative and significant effect on job satisfaction, job satisfaction had a negative and significant effect on turnover intention, job satisfaction mediated the effect of workload on turnover intention. These results have implications for human resource development, especially for HOMM Saranam Baturiti employees to pay more attention to workload and employee job satisfaction, so as to reduce turnover intention.